Reagent-Free Colorimetric Cholesterol Test Strip Based on Self Color-Changing Property of Nanoceria - Nguyen, Phuong Thy; Kim, Young Im; Kim, Moon Il (Frontiers in Chemistry, 2020)
Paper-based test strip consisting of cerium oxide nanoparticles (nanoceria) as hydrogen peroxide (H2O2)-dependent color-changing nanozymes and cholesterol oxidase (ChOx) has been developed for convenient colorimetric determination of cholesterol without the need for chromogenic substrate. The construction of the cholesterol strip begins with physical adsorption of nanoceria on the paper surface, followed by covalent immobilization of ChOx via silanization, chitosan-mediated activation, and glutaraldehyde treatment of the nanoceria-embedded paper matrices. In the presence of cholesterol, ChOx catalyzes its oxidation to produce H2O2, which forms peroxide complex on the nanoceria surface and induces visual color change of the nanoceria-embedded paper from white/light yellow into intense yellow/orange, which was conveniently quantified with an image acquired by a conventional smartphone with the ImageJ software. Using this strategy, target cholesterol was specifically determined down to 40 μM with a dynamic linear concentration range of 0.1 to 1.5 mM under neutral pH condition, which is suitable to measure the serum cholesterol, with excellent stability during 20 days and reusability by recovering its original color-changing activity for 4 consecutive cycles. Furthermore, the practical utility of this strategy was successfully demonstrated by reliably determining cholesterol in human blood serum samples. This study demonstrates the potential of self color-changing nanozymes for developing colorimetric paper strip sensor, which is particularly useful in instrumentation-free point-of-care environments.